MOTIVASI DAN DUKUNGAN SOSIAL KELUARGA MEMPENGARUHI KEPATUHAN BEROBAT PADA PASIEN TB PARU DI POLI PARU BP4 PAMEKASAN - Latifatul Muna; Umdatus Soleha (Jurnal Ilmiah Kesehatan, 2014)
Tuberculosis is the number three cause of death in Indonesia (results SKRT, 1995), one of the cause of death was a failure of TB treatment programs that are affected by treatment non compliance. Implementation of the treatment program should involve the patient's family and raise awareness to understand the importance of treatment. This study aimed to analyze the relationship between motivation, family social support with treatment compliance in patients with pulmonary tuberculosis in Pulmonary BP4 Poly (Hall Eradication and Prevention of Pulmonary Disease) Pamekasan. This study was an observational analytic study with cross sectional approach. Amount of samples of 16 outpatients selected by simple random sampling technique from the patient population undergoing treatment at Poly BP4 Pamekasan. Independent variables examined included family motivation and social support, while the dependent variable was treatment compliance. Data was collected through questionnaires spread sheets, data were analyzed using multiple logistic regression analysis. The results showed there was a negative relationship motivation with treatment compliance (OR = 0.67, p = 0.667) and there is a relationship of family social support with treatment compliance (OR = 20.0, p = 0.027). Multivariate test results were there is a relationship with sufficient strength among motivation (OR = 0.48, p = 0.589), family social support (OR = 21.99, p = 0.028) with treatment compliance.Conclusion of this study is a family of high social support will lead to higher compliance too. For tuberculosis treatment program required an awareness of the patient and family support